2005
DOI: 10.1111/j.1365-2133.2005.06508.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon (IFN)-gamma is a main mediator of keratinocyte (HaCaT) apoptosis and contributes to autocrine IFN-gamma and tumour necrosis factor-alpha production.

Abstract: Taken together, our data suggest a central role for IFN-gamma in HaCaT keratinocyte apoptosis but also show the importance of co-acting mediators such as TNF-alpha, TRAIL and FasL, which potentiate the effect of paracrine and autocrine IFN-gamma and TNF-alpha release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 28 publications
(45 reference statements)
5
43
0
Order By: Relevance
“…Elevated relative telomerase activity was more significant when cells were treated with TNF-α and IFN-γ together. Those results were similar to previous reports about the synergic effect of TNF-α with IFN-γ in the induction of keratinocyte apoptosis 20 . Interestingly, our results about the pattern of increased telomerase activity seemed to parallel with the inhibitory effect of TNF-α and IFN-γ on cultured human keratinocyte.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Elevated relative telomerase activity was more significant when cells were treated with TNF-α and IFN-γ together. Those results were similar to previous reports about the synergic effect of TNF-α with IFN-γ in the induction of keratinocyte apoptosis 20 . Interestingly, our results about the pattern of increased telomerase activity seemed to parallel with the inhibitory effect of TNF-α and IFN-γ on cultured human keratinocyte.…”
Section: Discussionsupporting
confidence: 82%
“…In the previous report about the effect of TNF-α in epidermal keratinocyte, it showed the inhibitory effect on cell proliferation 18 . IFN-γ also showed strong inhibitory effects on cell proliferation and these effects showed synergy in present action of TNF-α [19][20][21] . Our results showed significant inhibitory effects on cell proliferation in the early passage (P0, P1) of serial cultures.…”
Section: Discussionmentioning
confidence: 99%
“…HaCaT cells have been proposed to be more susceptible to TRAIL-induced apoptosis 22 compared with human epidermal keratinocytes (HEKs). A role for interferon (IFN)-␥ in TRAIL-induced apoptosis 23 of primary keratinocytes has recently been reported.…”
mentioning
confidence: 99%
“…It has been suggested that several pathways are implicated in the widespread apoptosis of keratinocytes in SJS/TEN (24)(25)(26)(27). Involvement of cytotoxic T cells and the molecular cytotoxicity of Fas and cytotoxic enzymes, including granzyme B, perforin, and granulysin have been shown in SJS/TEN (25,27).…”
Section: Discussionmentioning
confidence: 99%